The Struggle for Life: 'L'Assassinat Scientifique' in Daudet, Barrès, and Bourget. (2nd January 2019) - Belot, Françoise
ABSTRACT: Loosely based on a gruesome fait-divers from 1878, Paul Bourget's Le Disciple and L'Étape, Alphonse Daudet's La Lutte pour la Vie, and Maurice Barrès's Les Déracinés present the figure of the struggle-for-lifeur as a symptom and cause of social decomposition. In these novels and play, young men from the lower classes adopt the struggle for life as the guiding principle for their conduct. Each of these characters, using Darwinian principles as justification, commits or nearly commits a heinous crime, which Daudet called 'assassinat scientifique.' The authors associate this extreme version of social Darwinism with the Third Republic, and in particular with its educational policies. The protagonists' criminal acts serve as illustration and evidence of the republican system's moral failure. This article explores how these authors construct the struggle-for-lifeur as an emblematic figure of the Third Republic, but also how, in this cluster of fictions, they seek to rend science away from their political enemies in order to promote a socially and politically conservative agenda.